(3GdJUQja def YLR Yf GdJCdjas - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s ((3eMeO GdbjUjQi s)
(3ChdgG (B:s
(3Ghd GdeLdO GdChd CeG HYO jG Hfi , aEf CaVd GdYdhe HYO Yde GdOjf hcJGHg GdeHjf Yde GdWH ceG bGd QShd Gddg (B((3U(B) : (3Yde GdabjI ddGOjGf s
(3BNQgG (B:s
(3BNQ GdeLdO GdChd heG jQGg GdWHjH ef eRGL GdYdjd , hGdhbJ GdMGVQ , hUGdg , Ef TGA Gddg s
(3Gfgi fSN GdLRA GdChd SfI (B1093 (3g`s
(3UOQ cd LRA HagQS eaUd dehVhYGJs
(3bGd GHf CHj CUjHYI (B:" (3cJGH GdJUQjas
(3CcHQ JUGfjag hCTgQgG hgh JGe ai eYfGg (B" (3eLdOGf s
(3jTJedGf Ydi JSY hYTQjf ebGdI s
(3bQf GdfSN (B:s
Keywords: (3GdWHs